The Role of Entrepreneurship Education in the Double Track Program to Improve Students' Interest in Entrepreneurship at SMAN 1 Ngimbang - Saiful Arif; Siti Nur Khoiriyah; Sudarmiatin Sudarmiatin; Rizky Firmansyah (International Journal Business, Management and Innovation Review, 2024)
Entrepreneurial interest is needed by students to increase their self-confidence, as well as to foster positive character traits such as creativity, independence, and hard work. Students who have entrepreneurial skills tend to be more able to create jobs than look for jobs, which in turn can help reduce unemployment rates and improve community welfare. The purpose of this study was to determine the role of entrepreneurship education in the double track program to increase students' interest in entrepreneurship. The research method used qualitative descriptive descriptive qualitative methods by means of observation and interviews by going to the field. The location of this research was conducted at SMAN 1 Ngimbang, Lamongan Regency, East Java. Data analysis includes data reduction, data presentation, and data verification or conclusion. The researcher also used the source triangulation method and method triangulation to test the level of validity of the data. The results of the study found that